Analisis Kandungan Nutrisi pada Daging Tikus Hutan Ekor Putih (Maxomys hellwandii) - Kamagi, Decky W.; Rompas, Christny Ferdina; Bawole, Alpon Trisno (Universitas Negeri Manado, 2020)
White-tailed forest rats (Maxomys hellwandii) are other meat-producing animals that are consumed by the Minahasa community as exotic food. This study aims to determine the nutritional content of white-tailed forest rat meat. Nutrient content analysis was performed at the UNIMA chemistry laboratory and the BARISTAND laboratory in Manado. The procedure for this study is the analysis of nutrient content using the procedure of the Association of Official Analytical Chemists (AOAC 2005). The results of research on fresh forest rat meat showed the content of water, ash, fat, crude fiber, protein and carbohydrates 71.17%, 0.97%, 3.17%, 0.03%, 19, 16%, 5.53% and roasted forest rat meat, i.e. 69.14% water, 1.29% fat and 4.5% proteinÂ Â Â